Nonlinear relationships in bankruptcy prediction and their effect on the profitability of bankruptcy prediction models - Christian Lohmann; Steffen Möllenhoff; Thorsten Ohliger (Journal of Business Economics, 2022)
This study uses generalized additive models to identify and analyze nonlinear relationships between accounting-based and market-based independent variables and how these affect bankruptcy predictions. Specifically, it examines the independent variables that Altman (J Financ 23:589–609, 1968; Predicting financial distress of companies. Revisiting the Z-score and ZETA ® models. Working paper, 2000) and Campbell et al. (J Financ 63:2899–2939, 2008) used and analyzes what specific form these nonlinear relationships take. Drawing on comprehensive data on listed U.S. companies, we show empirically that the bankruptcy prediction is influenced by statistically and economically relevant nonlinear relationships. Our results indicate that taking into account these nonlinear relationships improves significantly several statistical validity measures. We also use a validity measure that is based on the profitability of the bankruptcy prediction models in the context of credit scoring. The findings demonstrate that taking into account nonlinear relationships can substantially increase the discriminatory power of bankruptcy prediction models.
Keywords: C53; D81; G33; M41; 650; Accounting-based information; Bankruptcy prediction; Profitability of credit scoring; Generalized additive model; Nonlinear relationships